In-situ synthesis of Cu2ZnSnS4/g-C3N4 heterojunction for superior visible light-driven CO2 reduction. (June 2022) - Raza, Adil; Haidry, Azhar Ali; Saddique, Jaffer
Abstract: Efficient solar to chemical energy conversion by promising semiconductor-based photocatalysis has gained huge interest due to being a potential solution for environmental remediation and energy problems. Though, the inadequate photogenerated charge separation practically limits the photocatalytic efficiency. Herein, mesoporous g-C3 N4 (CN) nanosheets coupled Cu2 ZnSnS4 (CZTS) hybrid composite as visible-light-driven photocatalyst is synthesized by a facile in situ hydrothermal self-assembly method and investigated for CO2 photocatalytic reduction. The hybrid composite shows a slight red shift to the visible region with enhanced optical absorption. Under visible light irradiation, experimental results exhibit CZTS-CN hybrid composite has CO/CH4 yield rates of 12.01/3.76 μmol g −1 after 5h, which are 1.54/1.41 times higher in comparison with bare CN. The heterojunction formation between CZTS and g-C3 N4 is restraining the electron-hole recombination and improves the photocatalytic performance. Finally, acceptable underlying mechanisms for CO2 photocatalytic reduction over CZTS-CN hybrid composite are proposed. This work may inspire readers to provide sufficient guidance to design high-performance photocatalysts. Highlights: Nobel metal/co-catalyst free CZTS/g-C3 N4 hybrid composite was developed. Enhanced light-harvesting was achieved by hybrid composite under visible-light. Heterojunction formation led to a higher electron-hole separation rate than g-C3 N4 . Synergistic effect between CZTS and g-C3 N4 enhanced photocatalytic efficiency. A suitable mechanism was proposed for improved photocatalytic performance.